A meta-analysis of idiopathic granulomatous mastitis treatments for remission and recurrence prevention - Ong, Seeu Si; Ho, Peh Joo; Liow, Jonathan Jun Kit; Tan, Qing Ting; Goh, Serene Si Ning; Li, Jingmei; Hartman, Mikael (Frontiers in Medicine, 2024)
Purpose The major aim of our meta-analysis was to review the effectiveness of various treatment modalities for achieving successful remission and preventing recurrence for women with idiopathic granulomatous mastitis (IGM). This knowledge is instrumental in developing evidence-based guidelines for clinicians to improve management strategies and outcomes for patients with IGM. Methods A systematic literature search was performed on MEDLINE (Ovid), Embase (Elsevier), PubMed, Cochrane Library, Web of Science, and Google Scholar; studies published to 19 January 2022 were included. A meta-analysis of 57 observational studies was performed. The results of two randomized controlled trials were also examined. Results There were 3,035 IGM patients across the observational and randomised studies. Overall recurrence and remission rates across all treatment strategies in 59 studies are 87.9% (2,667/3035) and 13.5% (359/2667), respectively. The studies reported 19 different treatment strategies, comprising observation, medical monotherapies, surgery, and combinations involving medical therapies, with and without surgery. Among monotherapy treatment, surgical management had the highest pooled remission rate (0.99 [95% confidence interval (CI) = 0.97–1.00]); among combination therapy, this was steroids and surgery (0.99 [0.94–1.00]). Antibiotic monotherapy had the lowest remission rate (0.72 [0.37–0.96]). The highest recurrence rates belonged to treatments that combined antibiotics and surgery (0.54 [0.02–1.00]), and antibiotics, steroids, and surgery (0.57 [0.00–1.00]). Most successful for preventing recurrence were observation (0.03 [0.00–0.10]), methotrexate (0.08 [0.00–0.24]), and steroids and surgery (0.05 [0.01–0.12]). There is a significant association between longer follow-up duration and recurrence rate reported, p = 0.002. Conclusion Combination therapies, especially those incorporating antibiotics, steroids, and surgery, have demonstrated higher remission rates, challenging the use of antibiotic monotherapy. There is an increased emphasis on the need for personalised, multi-pronged approach for preventing IGM recurrence, with longer follow-up care. More prospective future work in IGM research, with standardised diagnostic criteria, treatment protocols, and reporting guidelines will be important for developing treatment protocols and guidelines clinicians can adhere to in the clinical management of IGM patients. Systematic review registration: PROSPERO (CRD42022301386).